PENGARUH PERBEDAAN JENIS MEDIA TANAM TERHADAP PERTUMBUHAN SETEK Hoya coronaria BERBUNGA KUNING DARI KAWASAN HUTAN KERANGAS AIR ANYIR, BANGKA - Bella Febryskhia Putri; Yulian Fakhrurrozi; Sri Rahayu (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
The research to study the influence of the growing media on the growth of Hoya coronaria yellow flowered from Air Anyir heath forest, Bangka was carried out to know the best growing media. It is a first step to cultivate H. coronaria from the wild of the area. This research was done on September 2015 until January 2016 at trial house on Gabek II, Pangkalpinang. Growing media chemical analysis was done at Biology and MIPA laboratorium, Faculty of Agriculture, Fishery and Biology, Bangka Belitung University. This research used completely randomized factorial pattern using a single factor with 7 levels. The experiment was used seven different growing media podsol, red yellow podsolic (ultisol), moss, coco peat, podsol + ultisol, podsol + coco peat and podsol + moss. This research applied 3 replications with 3 Hoya cutting each of replication. Observed parameters were the establishment of cuttings (life cutting persentation), cutting growth persentation, shoot length, shoot diameter, roots total number, root length, leaves total numberand leaf wide. The result showed all growth parameters did not significantly different by the influence of different growing media. The best root growth is on PPMK (podsol+ultisol), while the best shoot growth and the best leaves growth are on the moss.